Redefining QRS transition to confirm left bundle branch capture during left bundle branch area pacing - Briongos-Figuero, Sem; Estévez Paniagua, Álvaro; Sánchez Hernández, Ana; Muñoz-Aguilera, Roberto (Frontiers in Cardiovascular Medicine, 2023)
Background QRS transition criteria during dynamic manoeuvers are the gold-standard for non-invasive confirmation of left bundle branch (LBB) capture, but they are seen in <50% of LBB area pacing (LBBAP) procedures. Objective We hypothesized that transition from left ventricular septal pacing (LVSP) to LBB pacing (LBBP), when observed during lead penetration into the deep interventricular septum (IVS) with interrupted pacemapping, can suggest LBB capture. Methods QRS transition during lead screwing-in was defined as shortening of paced V6-R wave peak time (RWPT) by ≥10 ms from LVSP to non-selective LBBP (ns-LBBP) obtained during mid to deep septal lead progression at the same target area, between two consecutive pacing manoeuvres. ECG-based criteria were used to compared LVSP and ns-LBBP morphologies obtained by interrupted pacemapping. Results Sixty patients with demonstrated transition from LVSP to ns-LBBP during dynamic manoeuvers were compared to 44 patients with the same transition during lead screwing-in. Average shortening in paced V6-RWPT was similar among study groups (17.3 ± 6.8 ms vs. 18.8 ± 4.9 ms for transition during dynamic manoeuvres and lead screwing-in, respectively; p = 0.719). Paced V6-RWPT and aVL-RWPT, V6-V1 interpeak interval and the recently described LBBP score, were also similar for ns-LBBP morphologies in both groups. LVSP morphologies showed longer V6-RWPT and aVL-RWPT, shorter V6-V1 interpeak interval and lower LBBP score punctuation, without differences among the two QRS transition groups. V6-RWPT < 75 ms or V6-V1 interpeak interval > 44 ms criterion was more frequently achieved in ns-LBBP morphologies obtained during lead screwing-in compared to those obtained during dynamic manoeuvres (70.5% vs. 50%, respectively p = 0.036). Conclusions During LBBAP procedure, QRS transition from LVSP to ns-LBBP can be observed as the lead penetrates deep into the IVS with interrupted pacemapping. Shortening of at least 10 ms in paced V6-RWPT may serve as marker of LBB capture.